Riset Pasar Biodiesel B20 di Indonesia: Evaluasi terhadap Produk dan Kesadaran Konsumen - Sachnaz Desta Oktarina; Ratnawati Nurkhoiry; M. Ansori Nasution; Suroso Rahutomo (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2019)
There are considerably limited evaluations had dealt with the demand side of the Indonesian B20 biodiesel market. Thus, market research on product performance, product importance, and consumer awareness was performed. This research utilized both qualitative and quantitative methods. In-depth interviews with key informants were summarized in the word cloud form. The outcomes then became the ground for quantitative research. The results of 111 online questionnaires indicated that there was a gap in the level of awareness among respondents in Sumatra to that of outside Sumatra. The male, higher education background, and heavy-user of bio solar cohort were tended to vote a sizeable number in the performance evaluation. Especially for the performance of biodiesel that caused sedimentation on the filter engines (73.08%, 72.35%, and 73.08%). Meanwhile, biodiesel performance that supports the nation's energy security is the most important attribute to be highlighted as the product main entity. The policy implication through multifaceted strategies such as incentive provision for automotive companies that are adaptive to market demand is one of a kind. In the long run, the return to investment from these policies are expected to not only increase the multiplier effects of the oil palm plantation but also national energy security.AbstrakSejauh ini belum ada evaluasi ilmiah yang mempelajari aspek permintaan produk biodiesel Indonesia dari sisi konsumen (pasar), sehingga studi mengenai evaluasi produk dan kesadaran konsumen biodiesel B20 menjadi tujuan dari penelitian ini. Riset pasar ini menggunakan metode kualitatif dan kuantitatif. Temuan dari riset kualitatif dalam bentuk wordcloud menjadi landasan untuk kajian kuantitatif. Hasil deskriptif dan nonparametrik 111 kuesioner secara daring mengindikasikan adanya kesenjangan tingkat kesadaran antara responden berdomisili di Sumatera dan luar Sumatera. Responden berjenis kelamin laki-laki, berlatar pendidikan tinggi, dan dominan menggunakan biosolar sebagai bahan bakarnya cenderung kritis menilai atribut terjadinya endapan pada mesin filter (73,08%; 72,35%; dan 73,08%). Performa biodiesel yang mendukung ketahanan energi bangsa menjadi aspek penting yang harus ditonjolkan sebagai entitas dari produk. Inovasi produk dapat dikembangkan melalui kebijakan multidimensi. Salah satunya dengan intervensi pemerintah melalui pemberian insentif bagi automaker yang adaptif terhadap permintaan pasar. Pada akhirnya, implikasi kebijakan ini diharapkan tidak hanya meningkatkan multiplyer effect dari perkebunan kelapa sawit, tetapi juga ketahanan energi nasional.